2007
DOI: 10.1016/j.cardiores.2007.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Life history of eNOS: Partners and pathways

Abstract: The complex regulation of eNOS (endothelial nitric oxide synthase) in cardiovascular physiology occurs at multiple stages. eNOS mRNA levels are controlled both at the transcriptional and post-transcriptional phases, and epigenetic mechanisms appear to modulate tissue-specific eNOS expression. The eNOS enzyme reversibly associates with a diverse family of protein partners that regulate eNOS sub-cellular localization, catalytic function, and biological activity. eNOS enzyme activity and sub-cellular localization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
342
0
6

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 348 publications
(357 citation statements)
references
References 139 publications
9
342
0
6
Order By: Relevance
“…5a). Evaluation of phosphorylated eNOS at Ser1177 [21] revealed that diabetes decreases eNOS phosphorylation at Ser1177 in the aorta of non-exercised db/db compared with those of WT mice (Fig. 5b); however, eNOS phosphorylation at Ser1177 was increased with both exercise intensities, with low-intensity exercise demonstrating a greater benefit.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…5a). Evaluation of phosphorylated eNOS at Ser1177 [21] revealed that diabetes decreases eNOS phosphorylation at Ser1177 in the aorta of non-exercised db/db compared with those of WT mice (Fig. 5b); however, eNOS phosphorylation at Ser1177 was increased with both exercise intensities, with low-intensity exercise demonstrating a greater benefit.…”
Section: Resultsmentioning
confidence: 98%
“…However, some studies suggest a downregulation of eNOS activity during diabetes [37]. Phosphorylation of eNOS is important for post-translational regulation of eNOS activity [21]. The activation of eNOS catalytic function by Ser1177 phosphorylation inhibits the dissociation of calmodulin from eNOS and so increases the rate of eNOS electron transfer to produce NO [21].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…6B). Increased eNOS activity under shear at 21% O 2 compared with shear at lower PO 2 levels may be due to differences in posttranslational protein modifications [nitrosylation, acylation, or phosphorylation of other sites, such as phosphorylation at Ser635 (5,8)] and/or alterations in interactions between eNOS and its regulatory proteins calmodulin, caveolin, HSP90, and platelet EC adhesion molecule-1 (3,22,25,50).…”
Section: Discussionmentioning
confidence: 99%